AKSELERASI DISTRIBUSI TECHNICAL SELLING MELALUI KNOWLEDGE SHARING PADA MEDIA SOSIAL: Studi Pada Store Ms Glow Kraksaan Probolinggo - Achmad Febrianto; Romzatul Widad; Riza Nur Aini (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2022)
The purpose of this study is to determine the acceleration of the distribution of technical selling through knowledge selling on social media. This study uses a qualitative type, namely descriptive data research in the form of sayings or pictures of people. Qualitative approaches can produce in-depth descriptions of the utterances, descriptions or results observed from each individual, group and community. Where this research was conducted with the support of primary and secondary data. The results of the Technical Selling Acceleration through Knowledge Sharing using social media marketing are proven. Of course, by implementing various business strategies ranging from sales strategies on social media with an AIDA basis (Attention, Interest Desire, and Action) as well as Knowledge Sharing for distributors who pay attention to several aspects such as Knowledge Value, Motivation in sharing knowledge, motivation, and the benefits provided for existing knowledge. With various methods applied both online and Offline Store, Ms. Glow Kraksaan continues to experience a significant increase. Even based on the data obtained, there are at least 30 store visitors every day. This goes linearly with the massive amount of information and marketing being carried out.